Comparative nutritional composition of selected grain sorghum varieties - Goldy, G.; Walters, T.; Lenssen, Andrew William; Riley, Jack G.; Posler, Gerry L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
For the 188 grain sorghum varieties studied, in vitro digestibilites were statistically similar, but there was a significant difference between the 12 production locations. Crude protein, calcium, and phosphorus levels indicated slight varietal differences; however, strong locational effects were evident.
Keywords: Beef; Grain sorghum; Digestibilities